Thick Space Approaches to Metropolitanism - Brantz, Dorothee; Disko, Sasha; Wagner-Kyora, Georg 1962- (Urban Studies, 2012)
Could the concepts of »metropolitanism« and »thick space« aid our understanding of historical and contemporary urban change? Essays by scholars from both sides of the Atlantic provide interdisciplinary approaches to the complex dynamics of large-scale urbanization. The book opens with conceptual questions regarding the development of metropoles and metropolitan studies. The following sections provide analyses of the social, environmental, and cultural dimensions of metropolitan spaces from both a theoretical and an empirical perspective, such as the role of planning and urban parks, the impact of ethnic diversity and segregation, the place of cinematic visions or the centrality of infrastructures and architecture